Health risk represented by inhaling polycyclic aromatic hydrocarbons (pah) during daily commuting involving using a high traffic flow route in bogota (2013)
Objective Assessing the risk to health by inhaling particles and particle-bound PAH during daily commuting along a high traffic flow route/corridor in Bogota.MethodsA van was equipped with a PAS2000 photo-electric sensor for real-time measurement of particle-bound PAH and a DustTrak for monitoringPM10 concentration; it drovealong typical commuting routes in the city. Exposure to particles and particle-bound PAH was assessed by using an inhalation intake model.Results A similar trend was observed for both PM10 and PAH concentration, indicating that traffic was the same source for both contaminants. Extreme PM10 and PAH inhalation concentrations were recorded every time direct bus and microbus emissions were measured by the van. Inhalation model results indicated that exposure was significantly greater when using avenues having mixed traffic use (i.e. buses, microbuses, passenger vehicles, motorcycles) compared to using roads where the TransMilenio system (articulated buses) had been implemented.Conclusions The results may support evaluating bus drivers, commuters and bike users’ exposure to toxic compounds in the city.